L’action sur les territoires face au défi d’une temporalité ouverte. L’improvisation comme modèle pour l’action aménagiste ? - Lisa Levy (Développement Durable et Territoires)
This article proposes an analysis of the main rationales of urban planning associated with three regimes of temporality: a. The linear and predictable temporality of planning, b. The uncertain and iterative temporality of the project, c. The open temporality of improvisation. Urban planning and projects propose to build the future through the development of visions and action plans. As their main goal is to control the process of action, they cannot fully accept uncertainty. Improvisation implies an epistemological and political turn that is necessary to imagine an open city. Building an open city means integrating surprise, ambiguity, and incompleteness, and relying on indeterminacy.